Chinese state owned enterprises and EU merger control, Alexandr Svetlicinii - Marta Teixeira Pires (Market and Competition Law Review)
This review intends to provide the reader with a general overview of the most recent work by Alexandr Svetlicinii: Chinese State Owned Enterprises and EU Merger Control. To this end, this review is divided into three major parts: (i) an introductory part, where the scope and relevance of the theme are presented; (ii) a second part containing a brief analysis of the book’s structure and content; and (iii) a conclusive critical analysis.